The Influence Of Leadership Style, Discipline, And Additional Employee Income On The Performance Of Employees Department Of Tourism, Youth, And Sports In Takalar ) - Rachman, Siswati; Yuliani, Nur Fadny (Jurnal Ekonomi Balance, 2022)
This study aims to analyze the effect of leadership style, application of discipline, and additional income on employee performance at the Department of Tourism, Youth and Sports of Takalar Regency. The type of research used is quantitative, which is a method used to answer research problems related to data in the form of numbers and statistical programs. The research was conducted from April to July 2021. The results showed that leadership style had a positive and partially significant effect on employee performance, discipline had a partially positive and significant effect on employee performance, and additional income had a partially positive and significant effect on employee performance because t count for the three independent variables is greater than t table. As for the F table value generated in this study is 2.859, while the calculated F value in the simultaneous test is 44, 633 which means the calculated F value > F table. In the next measurement it is known that the resulting significance value is 0.000 < 0.05. So, based on the results of testing and decision making in simultaneous testing, it can be concluded that the independent variables consisting of leadership style, discipline, and additional income simultaneously or together have a positive and significant effect on employee performance